Redesign Drainage System and Infiltration Wells Design in Lampung University (Case Study: UNILA Statue-Al-Wasii Mosque) - yunianto, mohammad lutfi; Purwadi, Ofik Taufik; Romdania, Yuda (Jurnal Rekayasa Sipil dan Desain, 2018)
Drainage is a wayÂ  for removal of excess water with a solution about excess of water. Nevertheless, a lot of drainage systems have a bad performance and out of its function. One of them is drainage system in Lampung University around Al-Wasiâi Mosque-Lampung University statue. One of the solution is environmental arrangement and one of the environmental arrangement is redesign of drainage system. It aim for resolve some flood inundationthat happenedÂ  in the rain because failed optimilize in drainage system aroun Al-Wasiâi Mosque-Lampung University statue. The analysis conducted in this research includes hydrology analysis and hydraulics analysis using HEC-RAS 4.1.0 application. Hydrology analysis aims to calculate the design discharge using rational, haspers and weduwen methods and modeling with HEC-RAS 4.1.0 application aims to determine the capacity of the water levelÂ  existing channel. So it can be known where the position of the flood point and planning the new channel dimensions. Based on the analysis, the need for dredging at D8-D10 indicating the occurrence of run offÂ  and inundation at across of Al-Wasiâi Mosque. Planning of infiltration wells is also very needed to overcome the problem of frequent flooding in Faculty of Engineering. It is also necessary to decrease run-off discharge in channel around Al-Wasiâi mosqueâs areas.The necessary is did concrete lining in base and two-side of channel.Â